Modification and patterning of nanometer-thin poly(ethylene glycol) films by electron irradiation - Meyerbröker, Nikolaus; Zharnikov, Michael (ACS applied materials & interfaces, 2013)
In this study, we analyzed the effect of electron irradiation on highly cross-linked and nanometer-thin poly(ethylene glycol) (PEG) films and, in combination with electron beam lithography (EBL), tested the possibility to prepare different patterns on their basis. Using several complementary spectroscopic techniques, we demonstrated that electron irradiation results in significant chemical modification and partial desorption of the PEG material. The initially well-defined films were progressively transformed in carbon-enriched and oxygen-depleted aliphatic layers with, presumably, still a high percentage of intermolecular cross-linking bonds. The modification of the films occurred very rapidly at low doses, slowed down at moderate doses, and exhibited a leveling off behavior at higher doses. On the basis of these results, we demonstrated the fabrication of wettability patterns and sculpturing complex 3D microstructures on the PEG basis. The swelling behavior of such morphological patterns was studied in detail, and it was shown that, in contrast to the pristine material, irradiated areas of the PEG films reveal an almost complete absence of the hydrogel-typical swelling behavior. The associated sealing of the irradiated areas allows a controlled deposition of objects dissolved in water, such as metal nanoparticles or fluorophores, into the surrounding, pristine areas, resulting in the formation of nanocomposite patterns. In contrast, due to the distinct protein-repelling properties of the PEG films, proteins are exclusively adsorbed onto the irradiated areas. This makes such films a suitable platform to prepare protein-affinity patterns in a protein-repelling background.
Gesehen am 21.05.2021